Evaluation Study of Free Spanning Subjected to Hydrodynamic Loads (Journal of University of Babylon for Engineering Sciences, 2018)
Suspended spans generally occur in subsea pipelines as a result of the irregularity of seabed. Additionally the suspended spans mostly result from the scouring phenomena around the installed non-buried pipeline. So as to discuss the hydrodynamic surrounding the pipeline and determining the significant deflections and associated stresses of the subsea pipeline in unsupported part, therefore, it’s very necessary to study the hydrodynamic surrounding the pipeline in detail. A two main aims have been done in this study, first assess the stresses at free span section and the second one was the effect of soil characteristics in contact area between pipeline and the seabed soil. A combined model of stresses/lateral displacement has been made. An ANSIS model has been built on the offshore pipelines as a consequence of the combined hydrodynamic loads such as wave/current effects. The calculations have been computed by using the finite element method for the free span to describe the surrounding environment in more accuracy. The pipeline stresses intensity increases with closing to free span center. This is attributed to the fact that UY and UZ have more maximum values at these region.